A Reflection on Plagiarism, Patchwriting, and the Engineering Master's Thesis. - Edward J. Eckel (Issues in Science and Technology Librarianship, 2010)
The author reflects on the issues of plagiarism and source attribution faced by graduate students in the sciences and technology fields. He believes that it is a result of the disconnection between expectations on the students and the way they are being educated to satisfy those expectations. He discusses patchwriting, where a writer incorporates parts of verbatim source text into their own writing due to a lack of understanding of the sources that leads to inadequate paraphrasing, and its difference with plagiarism.